Desenvolvimento e validação de métodos analíticos para o doseamento de daptomicina injetável - Christ, Ana Paula (2013)
This work presents the development and validation of analytical methods to assay daptomycin injection. Daptomycin is a drug of a new class of antibiotics, known as cyclic lipopeptides. It was approved in USA in 2003 and in Brazil in 2009. Up to now, there are no reports about methods to assay the drug in pharmaceutical products, both in scientific literature or in official compendia. Methods to identify daptomycin in raw material were realized as solubility, melting point, infrared spectrophotometry (IR), ultraviolet spectrophotometry (UV) and differential scanning calorimetry (DSC) and they showed appropriate results. The following methods to assay daptomycin injection were developed and validated: high performance liquid chromatography (HPLC), microbiological assay (turbidimetric) and UV-spectrophotometry. All of them were validated according current guidelines, by the following parameters: specificity, linearity, precision, accuracy and robustness, being all the requirements met. The mean values of daptomycin assay by the three methods were: 100,23 ± 0,59% (HPLC); 100,96 ± 2,58% (turbidimetric assay) and 98,98 ± 1,35% (UV-spectrophotometry). They were compared by ANOVA, which indicated that HPLC and turbidimetric assay are interchangeable. The stress testing showed that daptomycin is very susceptible to alkaline medium and that the degradation follows first order kinetic, in the conditions adopted. It was found that the degradation product(s) of daptomycin do not have antimicrobial activity. Considering their characteristics, HPLC and turbidimetric assays can be used in routine quality control and in stability studies of daptomycin injection.